2021
DOI: 10.1371/journal.pone.0246469
|View full text |Cite
|
Sign up to set email alerts
|

OCT-angiography: Regional reduced macula microcirculation in ocular hypertensive and pre-perimetric glaucoma patients

Abstract: Purpose OCT-angiography (OCT-A) offers a non-invasive method to visualize retinochoroidal microvasculature. As glaucoma disease affects retinal ganglion cells in the macula, macular microcirculation is of interest. The purpose of the study was to investigate regional macular vascular characteristics in patients with ocular hypertension (OHT), pre-perimetric primary open-angle glaucoma (pre-POAG) and controls by OCT-A in three microvascular layers. Material and methods 180 subjects were recruited from the Erl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
0
19
0
3
Order By: Relevance
“…We revealed that the most sensitive parameters of OCT were superior ganglion cell complex (GCC) thickness with AUC = 0.860 (p < 0.001) and the sensitivity at the best cut-off value = 90% (Table 3). With the development of optical coherence tomography angiography (OCTA), the perfusion of the optic disc and macula was considered as an early indicator of glaucomatous change, with a reported AUC of macular vascular density = 0.88 [23] and a significantly decreased circumpapillary vascular density [22]. We reported that the most sensitive parameters of OCTA was the whole image of radial peripapillary capillary (RPC) density with AUC = 0.791 (p < 0.001) and sensitivity at the best cut-off value = 70% (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We revealed that the most sensitive parameters of OCT were superior ganglion cell complex (GCC) thickness with AUC = 0.860 (p < 0.001) and the sensitivity at the best cut-off value = 90% (Table 3). With the development of optical coherence tomography angiography (OCTA), the perfusion of the optic disc and macula was considered as an early indicator of glaucomatous change, with a reported AUC of macular vascular density = 0.88 [23] and a significantly decreased circumpapillary vascular density [22]. We reported that the most sensitive parameters of OCTA was the whole image of radial peripapillary capillary (RPC) density with AUC = 0.791 (p < 0.001) and sensitivity at the best cut-off value = 70% (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…PP is considered to be an important instrument in evaluating early glaucoma, especially in the pre-perimetric stage. Additionally, OCTA has been used to evaluate the vessel density changes in PPG [22][23][24][25][26][27][28][29][30][31], while its diagnostic value has not been completely established.…”
Section: Introductionmentioning
confidence: 99%
“…B. mit Fibrosierung) verfolgt werden [13,19,20]. Auch die Glaukomdiagnostik nutzt die Darstellung der signifikant verringerten Gefäßdichte parapapillär [21 -23] und im Makulabereich [24,25], sodass sie bereits als mögliches neues Frühdiagnostikum postuliert wird [26,27]. Die OCT-A ist aber nicht nur für uns Ophthalmologen von Bedeutungda man aktuell nur an 2 Stellen in vivo die Kapillaren beim Menschen visualisieren und quantifizieren kann: am Nagelfalz und der Retina.…”
Section: Einsatzbereiche Der Oct-a-methodikunclassified
“…Patients with PEXS showed PEX material deposits in the anterior chamber, but without any signs of glaucoma (Scharfenberg and Schlotzer-Schrehardt, 2012;Hohberger et al, 2019b).…”
Section: Pex Syndromementioning
confidence: 99%